Protecting Photo Copyrights Against Unauthorized Reuploads on E-commerce Platforms - Soulthoni, Hannin Pradita Nur; Permata, Rika Ratna; Wijayanti, Dewi Y (International Journal of Qualitative Research, 2024)
Copyright infringement on e-commerce platforms is a growing concern, especially with the unauthorized use of individuals' photos for commercial purposes. Eliska's case highlights the negative consequences of uploading product photos without permission, violating the moral and economic rights of the original owners. Indonesia's Copyright Law No. 28 of 2014 imposes serious legal sanctions on such violations, holding individuals and e-commerce platforms like Tokopedia accountable for monitoring and enforcing copyright rules. This research uses normative legal methods to analyze regulations, licensing, and copyright protection related to photography and portraits in e-commerce, focusing on Tokopedia. A descriptive-analytical approach is employed to explain legal regulations concerning copyright in product sales on the platform, with data collected through theoretical literature review, legislative analysis, and online studies. Findings indicate that copyright infringement on e-commerce platforms significantly impacts original owners and the integrity of online commerce. Eliska's case shows how unauthorized photo use can lead to financial loss and reputation damage. Law No. 28 of 2014 provides for criminal sanctions and fines for such violations, while e-commerce platforms must ensure compliance with copyright regulations. Legal certainty and collaboration between copyright owners and platforms are essential for a safe and fair online trading environment.